1987
DOI: 10.1113/jphysiol.1987.sp016535
|View full text |Cite
|
Sign up to set email alerts
|

Actions of single sensory fibres on cat dorsal column nuclei neurones: vibratory signalling in a one‐to‐one linkage.

Abstract: 1. The synaptic linkage between single, identified sensory fibres associated with Pacinian corpuscle (P.c.) receptors and central neurones of the dorsal column nuclei was examined in decerebrate or anaesthetized cats. Paired recordings were made from individual neurones in the gracile division of the dorsal column nuclei and from the hind‐limb interosseous nerve in which it is possible to identify and monitor the activity of each P.c. fibre activated when recording from the intact nerve with a platinum hook el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
2

Year Published

1987
1987
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 45 publications
4
40
2
Order By: Relevance
“…inputs were carried out on cats from the earlier series (Ferrington et al 1987b) and all procedures with the exception of those outlined below were described in that paper. Five additional experiments were performed in adult cats, to investigate whether convergent P.c.…”
Section: Methodsmentioning
confidence: 99%
“…inputs were carried out on cats from the earlier series (Ferrington et al 1987b) and all procedures with the exception of those outlined below were described in that paper. Five additional experiments were performed in adult cats, to investigate whether convergent P.c.…”
Section: Methodsmentioning
confidence: 99%
“…This capacity for selective recruitment of different fibres together with the excellent signal-to-noise ratio attainable from the indicis proprius nerve in continuity, permitted unequivocal monitoring and identification of each active fibre. These attributes make this limb nerve preparation just as suitable as those we have used previously for the purpose of examining the central actions of single identified sensory nerve fibres of other classes, in particular the PC, SAI, SAII and joint afferent fibre classes (Ferrington et al 1987;Vickery etal. 1994;Gynther etal.…”
Section: Discussionmentioning
confidence: 98%
“…As recorded fibres were sensitive to manual stretch applied longitudinally to the muscle tendon they were assumed to be associated with muscle spindles, whose locations were then identified by mechanical probing of the muscle by means of a fine (0.5-2 mm diameter) glass probe. Once the receptor's location was established, a mechanical stimulator (Ferrington et al 1987;Mackie et al 1995) was used to apply controlled stimuli (steady displacement or trains of sinusoidal vibration) to the focus of maximum sensitivity. It appeared that all fibres studied were of the group la class of account of their high sensitivity to both longitudinal and focal vibration (Brown et al 1967).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Should these reliable signals of vibrotactile events in the SAII fibres not be used for the behavioural aspects of vibrotactile sensibility in hairy skin it may mean that the central transmission of their signals is poorer than that for other classes such as the PC fibres. We have shown that the latter group has a remarkable security of transmission that preserves temporal patterning across the synaptic linkage of the dorsal column nuclei (Ferrington et al 1986(Ferrington et al , 1987a. The issue of central transmission of SAII and SAI signals is currently under investigation in our laboratory.…”
Section: Discussionmentioning
confidence: 99%